Transoral Laser Microsurgery and Transoral Robotic Surgery in Aging Patients: A State-of-The-Art Review - Lechien JR (Clinical Interventions in Aging)
Jerome R Lechien1– 3 1Polyclinic of Poitiers, Elsan Hospital, Poitiers, France; 2Department of Surgery, Mons School of Medicine, UMONS Research Institute for Health Sciences and Technology, University of Mons (UMONS), Mons, Belgium; 3Department of Otolaryngology-Head and Neck Surgery, Foch Hospital, Paris Saclay University, Paris, FranceCorrespondence: Jerome R Lechien, Chairman and Professor of Surgery, Department of Surgery, University of Mons, Mons, Belgium, Tel +32 65 37 35 84, Email Jerome.Lechien@umons.ac.bePurpose: In the present study, the findings related to the epidemiology, clinical presentation, and therapeutic outcomes of elderly patients treated with transoral laser microsurgery (TOLM) and transoral robotic surgery (TORS) for supraglottic laryngeal squamous cell carcinoma (LSCC) have been reviewed.Methods: A PubMed, Cochrane Library, and Scopus literature search was conducted according to the PRISMA statements. Critical literature analysis was carried out considering the last advancement in TOLS and TORS, and their related surgical, functional, and survival outcomes.Findings: The mean age of patients with supraglottic LSCCs has progressively increased in the past decades. The data on postoperative complications in elderly patients with LSCC are heterogeneous and contradictory. The thought of the age-related high risk of complications was based on open supraglottic laryngectomy (SGL), but not on TOLM and TORS findings, which do not support an age-related increase of most postoperative complications. The only complication that could be associated with age is aspiration. The adequate selection of patients undergoing TOLM or TORS, and the pre- to postoperative evaluation of swallowing function can prevent this risk. The OS of elderly patients treated with TOLM or TORS SGL could be lower compared to younger patients. However, the disease-free survival was not influenced by age, highlighting the role of comorbidities and intercurrent diseases in the presumed lower survival. The survival analysis could definitively consider the physiological age rather than the chronological age to investigate the impact of age on survival outcomes.Conclusion: The current literature supports an important place of TOLM and TORS in managing cT1-T3 supraglottic LSCC. The preoperative geriatric, nutritional, and swallowing evaluations are important for ensuring an adequate selection of patients treated with TORS or TOLM SGL.Keywords: larynx, carcinoma, cancer, otolaryngology, head neck, surgery, transoral, laser, robotic, TORS, elderly, aging, age